Analisa Manajemen Risiko Pada Perusahaan Real Estate X - Weol, Anthony Loana; Wibowo, Adi; Dewi, Lily Puspa (Jurnal Infra, 2015)
Real Estate company X has the IT division that provides support and services to another divisions which became a customer for the IT division. IT division provides services such as procurement of software, hardware assembly, and service divisions helpdesc for the needy. The problems that have occurred on the company network is lost, which caused the saturation point in the cable resulting data is entered into a computer can not be transferred to the server, the server is full, because any existing data within the company will be put into memory on the server, and often memory capacity in the server is no longer enough to accommodate the existing data, and the damage - hardware damage caused by the negligence of the user. That requires a risk analysis of quality management and risk management to cope with risks that exist.In this thesis, risk assessments of the quality management and risk management in IT services was carried out. The author uses several sources to help understand and assess the factors - existing risk factors, namely COBIT 4.1, ISO 31000, and Risk Rating Metodhology by OWASP. Based on research and interviews conducted, it was found several risk factors such as lack of Quality Management System that is used to guide the IT division, the absence of a structured risk management at the company, and the absence of criteria for determining the likelihood and impact for risks that were found.Responses should be done by the company is making a Quality Management System that can be used to provide guidance and guidance for IT divisions to carry out the duties and obligations, and implement a risk management used to identify, analyze, and identify ways how to prevent and avoid risks occurs.